2009
DOI: 10.4049/jimmunol.0902505
|View full text |Cite
|
Sign up to set email alerts
|

The Pleckstrin Homology Domain Adaptor Protein Bam32/DAPP1 Is Required for Germinal Center Progression

Abstract: Ab affinity maturation within germinal centers (GCs) requires weeks to complete. Several signaling pathways in B cells have been shown to be required for initiation of the GC response; however, the signaling checkpoints controlling progression and eventual dissolution of the GC reaction are poorly understood. The adaptor protein Bam32/DAPP1 was originally isolated from human GCs and functions downstream of phosphoinositide 3-kinase enzymes, which are known to have critical roles in B cell activation and GC res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
3
16
0
Order By: Relevance
“…We have recently found evidence supporting a role for Bam32 in T-dependent Ab responses (36). Upon immunization with Tdependent Ag, GCs initiate normally in Bam32-deficient mice, but subsequently collapse, resulting in impaired affinity maturation.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We have recently found evidence supporting a role for Bam32 in T-dependent Ab responses (36). Upon immunization with Tdependent Ag, GCs initiate normally in Bam32-deficient mice, but subsequently collapse, resulting in impaired affinity maturation.…”
Section: Discussionmentioning
confidence: 94%
“…All B cell subsets develop normally in Bam32-deficient mice, but they show markedly impaired T-independent Ab responses (32,35). In contrast, Bam32-deficient mice were reported to mount quantitatively normal responses to T-dependent Ag; however, we recently found that Bam32 deficiency leads to premature dissolution of GCs and impaired affinity maturation (36).…”
mentioning
confidence: 86%
“…DOCK8 is a member of the DOCK family, whose members contain a DOCK homology region 1 domain (DHR1), which recruits them to PIP3, and have Rho-Rac family GTP-exchange factor activity. Another PIP3-binding protein, Bam32, which is a pleckstrin homology domain adapter protein, was also found to be important for BCR-induced integrin adhesion and spreading as well as the formation of stable conjugates with T cells (107), and Bam32 deficiency resulted in a failure of GCs to persist after formation and a reduction in affinity maturation (108). Bam32-deficient GC B cells were more susceptible to apoptosis.…”
Section: Pi3k Signaling In Gc B-cell Selection and Persistencementioning
confidence: 99%
“…Bam32 was found to be expressed mainly in murine hematopoietic cells but also in human cells, including B and T lymphocytes. It has multiple functions in B cell activation and is required for biological responses including BCR-induced proliferation, Ab responses to type II T-independent Ags, germinal center progression, and formation of polarized conjugates with T cells (11)(12)(13)(14). It functions by regulating F-actin formation, and this Bam32-induced cytoskeletal rearrangement has been shown to be important for receptor endocytosis and membrane ruffling (15,16).…”
Section: Endritic Cells (Dc) Are Professional Apcs With a Uniquementioning
confidence: 99%